Investigation of the mechanism of the anomalous Hall effects in Cr2Te3/(BiSb)(2)(TeSe)(3) heterostructure - Cho, Seong Won; Lee, In Hak; Lee, Youngwoong; Kim, Sangheon; Khim, Yeong Gwang; Park, Seung-Young; Jo, Younghun; Choi, Junwoo; Han, Seungwu; Chang, Young Jun; Lee, Suyoun (Springer | Korea Nano Technology Research Society, 2023)
The interplay between ferromagnetism and the non-trivial topology has unveiled intriguing phases in the transport of charges and spins. For example, it is consistently observed the so-called topological Hall effect (THE) featuring a hump structure in the curve of the Hall resistance (R-xy) vs. a magnetic field (H) of a heterostructure consisting of a ferromagnet (FM) and a topological insulator (TI). The origin of the hump structure is still controversial between the topological Hall effect model and the multi-component anomalous Hall effect (AHE) model. In this work, we have investigated a heterostructure consisting of BixSb2-xTeySe3-y (BSTS) and Cr2Te3 (CT), which are well-known TI and two-dimensional FM, respectively. By using the so-called "minor-loop measurement ", we have found that the hump structure observed in the CT/BSTS is more likely to originate from two AHE channels. Moreover, by analyzing the scaling behavior of each amplitude of two AHE with the longitudinal resistivities of CT and BSTS, we have found that one AHE is attributed to the extrinsic contribution of CT while the other is due to the intrinsic contribution of BSTS. It implies that the proximity-induced ferromagnetic layer inside BSTS serves as a source of the intrinsic AHE, resulting in the hump structure explained by the two AHE model. [GRAPHICS] .